Land use/cover classification- An introduction review and comparison (Global Journals of Research in Engineering, 2012)
Accurate and reliable information about land use and land cover is essential for change detection and monitoring of the specified area. It is also useful in the updating the geographical information about the area. Over the past decade, a significant amount of research has been conducted concerning the application of different classifier and image fusion technique in this area. In this paper, introductions to the land use and land cover classification techniques are given and the results from a number of different techniques are compared. It has been found that, in general fusion technique perform better than either conventional classifier or supervised/unsupervised classification.
Keywords: Land Cover Land; Fusion; Multiresolution; supervised; unsupervised